Physicochemical characteristics of self-assembled nanoparticles based on glycol chitosan bearing 5 beta-cholanic acid - Kwon, S; Park, JH; Chung, H; Kwon, IC; Jeong, SY; Kim, IS (AMER CHEMICAL SOC, 2003)
The self-aggregation behavior and microscopic characteristics of hydrophobically modified glycol chitosans (HGCs), prepared by covalent attachment of 5beta-cholanic acid to glycol chitosan, were investigated by using H-1 NMR, dynamic light scattering, fluorescence spectroscopy, and transmission electron microscopy (TEM). The HGCs formed self-aggregates in an aqueous phase by intra- or intermolecular association between hydrophobic 5beta-cholanic acids attached to glycol chitosan. The critical aggregation concentrations (cacs) of the HGCs were dependent on the degree of substitution (DS) of 5beta-cholanic acid and were significantly lower than those of low molecular weight surfactants. The mean diameters of the self-aggregates decreased with the increase in the DS of 5beta-cholanic acid because of the formation of compact hydrophobic inner cores. The TEM images demonstrated that the shape of the self-aggregates, on the basis of the HGCs, is spherical. The partition equilibrium constants (K-v) of pyrene, measured in the self-aggregate solutions of the HGCs, indicated that the increase in the DS enhances the hydrophobicity of inner core of self-aggregates. The aggregation number of 5beta-cholanic acid per one hydrophobic microdomain, estimated by the fluorescence quenching method using cetylpyridinium chloride, increased with increasing the DS, which suggested that several HGC chains were needed to form one hydrophobic domain.
Keywords: POLYION COMPLEX MICELLES; BLOCK-COPOLYMERS; SODIUM TAURODEOXYCHOLATE; POLY(ETHYLENE GLYCOL); HYDROGEL NANOPARTICLE; AGGREGATION NUMBER; BILE-SALT; IN-VITRO; DELIVERY; WATER